(untitled) (Baghdad Science Journal, 2025)
Multiple studies support a role for inflammation in the pathogenesis of coronary atherosclerosis and unstable cardiac syndromes. However, of the known pro-inflammatory cytokines, only elevated plasma levels of interleukin-6(IL-6) have been linked to Unstable Angina. We sought to examine the plasma levels of other major proinflammatory cytokines in similar clinical settings patients with unstable angina and acute myocardial infarction and the relationship extent between them. This study aimed to investigate and compare the level of IL-1 in Unstable Angina and Acute Myocardial Infarction patients. Thirty patients with unstable angina and thirty patients with Acute Myocardial Infarction, also thirty healthy individual as control were included in this study to measure the levels of IL-1alpha, lipid profile and Body Mass Index. There was a significant increase in the level of IL-1 ? in patients with acute myocardial infarction or with unstable angina compared with control group. IL-1 ? positively correlated with total cholesterol, triglycerides, Low Density Lipoprotein and Very Low Density Lipoprotein, while there was a negative correlation with High Density Lipoprotein. In conclusionInterleukin-1 ? significantly increases in patients with acute myocardial infarction or with unstable angina. There was no significant difference in level of IL-1? between AMI and unstable angina patients.